Dietary organosulfur compounds: Emerging players in the regulation of bone homeostasis by plant-derived molecules - Gambari, Laura; Grigolo, Brunella; Grassi, Francesco (Frontiers in Endocrinology, 2022)
The progressive decline of bone mass and the deterioration of bone microarchitecture are hallmarks of the bone aging. The resulting increase in bone fragility is the leading cause of bone fractures, a major cause of disability. As the frontline pharmacological treatments for osteoporosis suffer from low patients’ adherence and occasional side effects, the importance of diet regimens for the prevention of excessive bone fragility has been increasingly recognized. Indeed, certain diet components have been already associated to a reduced fracture risk. Organosulfur compounds are a broad class of molecules containing sulfur. Among them, several molecules of potential therapeutic interest are found in edible plants belonging to the Allium and Brassica botanical genera. Polysulfides derived from Alliaceae and isothiocyanates derived from Brassicaceae hold remarkable nutraceutical potential as anti-inflammatory, antioxidants, vasorelaxant and hypolipemic. Some of these effects are linked to the ability to release the gasotrasmitter hydrogen sulfide (H2S). Recent preclinical studies have investigated the effect of organosulfur compounds in bone wasting and metabolic bone diseases, revealing a strong potential to preserve skeletal health by exerting cytoprotection and stimulating the bone forming activity by osteoblasts and attenuating bone resorption by osteoclasts. This review is intended for revising evidence from preclinical and epidemiological studies on the skeletal effects of organosulfur molecules of dietary origin, with emphasis on the direct regulation of bone cells by plant-derived polysulfides, glucosinolates and isothiocyanates. Moreover, we highlight the potential molecular mechanisms underlying the biological role of these compounds and revise the importance of the so-called ‘H2S-system’ on the regulation of bone homeostasis.